The Relationship Between Metabolic Syndrome Awareness and Perception of Health in Exercise Participants: A Cross-Sectional Study - Avcu, Gokce; Akbulut, Taner; Avcu, Emsal cagla; Migliaccio, Gian Mario (Mdpi, 2025)
Background and Objectives: The level of knowledge and awareness individuals have about diseases, as well as their health perceptions, can influence healthy lifestyle behaviors. The aim of this study is to evaluate the level of knowledge and awareness about metabolic syndrome (MetS) and the level of health perception, as well as to investigate the relationship between MetS knowledge and awareness and health perceptions. Materials and Methods: This research study was carried out using a cross-sectional survey model. The study group consisted of a total of 446 participants, including 328 men and 118 women, with an average age of 27.10 +/- 8.86 years. In this study, the Metabolic Syndrome Knowledge and Awareness Scale (MSKAS) was used to assess metabolic syndrome awareness, and the Perception of Health Scale (PHS) was used to assess the perception of health. Results: The MetS knowledge and awareness level and the health perception of individuals attending sports centers are at a moderate level, and a weak but significant positive relationship has been found between MetS knowledge and awareness and health perception. Moreover, MSKAS scores were higher in women (p < 0.05). Participants who were knowledgeable about chronic diseases had higher MSKAS and PHS scores (p < 0.05). Those with a family history of chronic disease had higher PHS scores (p < 0.05). Participants who tracked their daily caloric intake had higher PHS scores (p < 0.05). Additionally, those who monitored their daily step count had higher MSKAS and PHS scores (p < 0.05). Conclusions: These findings suggest that the levels of MetS knowledge and awareness, as well as health perception, may vary depending on various individual and behavioral factors among individuals attending fitness centers.
Keywords: metabolic syndrome; health; physical activity; lifestyle